(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: This study evaluated in vitro the influence of an eugenol-based sealer (EndoFill) on the retention of stainless steel prefabricated posts cemented with zinc phosphate and resin-based (Panavia F) cements after different periods of root canal obturation, using the pull-out test. MATERIAL AND METHODS: Sixty upper canines were decoronated and the roots were embedded in resin blocks. The specimens were distributed into 3 groups, according to the period elapsed between canal obturation and post cementation: Group I - immediately; Group II - 72 h and Group III - 4 months. The groups were subdivided according to the type of cement used for post cementation: A - zinc phosphate and B - Panavia F. Following the experimental periods, specimens were subjected to pullout test in an Instron machine with application of tensile force at a crosshead speed of 0.5 mm/min until post dislodgement. The maximum forces required for post removal were recorded (kN) and means were subjected to statistical analysis by 2-way ANOVA and Tukey-Kramer test (α=0.001) RESULTS: There were statistically significant differences (p;0.05) were found between the three post cementation periods, regardless of the cement. CONCLUSIONS: It was concluded that the eugenol-based sealer influenced the tensile strength of the posts cemented with the resin cement, but had no influence on the time waited between root canal obturation and post space preparation/post cementation.